Genotoxicity evaluation of 2, 4-D, dicamba and glyphosate alone or in combination with cell reporter assays for DNA damage, oxidative stress and unfolded protein response. (November 2021) - Mesnage, Robin; Brandsma, Inger; Moelijker, Nynke; Zhang, Gaonan; Antoniou, Michael N.
Abstract: The current generation of carcinogenicity tests is often insufficient to predict cancer outcomes from pesticide exposures. In order to facilitate health risk assessment, The International Agency for Research on Cancer identified 10 key characteristics which are commonly exhibited by human carcinogens. The ToxTracker panel of six validated GFP-based mouse embryonic stem reporter cell lines is designed to measure a number of these carcinogenic properties namely DNA damage, oxidative stress and the unfolded protein response. Here we present an evaluation of the carcinogenic potential of the herbicides glyphosate, 2, 4-D and dicamba either alone or in combination, using the ToxTracker assay system. The pesticide 2, 4-D was found to be a strong inducer of oxidative stress and an unfolded protein response. Dicamba induced a mild oxidative stress response, whilst glyphosate did not elicit a positive outcome in any of the assays. The results from a mixture of the three herbicides was primarily an oxidative stress response, which was most likely due to 2, 4-D with dicamba or glyphosate only playing a minor role. These findings provide initial information regarding the risk assessment of carcinogenic effects arising from exposure to a mixture of these herbicides.